KUALITAS AIR DAN PERSEPSI WISATAWAN DI KAWASAN WISATA ALAM PULAU PINUS KALIMANTAN SELATAN - Khairun Nisa; Januar Arthani (Lambung Mangkurat University-Indonesia, 2011)
This research was carried out in Pulau Pinus area. The objectives of this research was to analisis the quality of water resources that available in Pulau Pinus and tourist perception about nature based tourism. In this research, both field and laboratory observation were done. Data collected include : primary data such as water quality and tourist perception. It was analyzed based on field and laboratory observation to examine its chemical and physical characteristics. Water quality of the Kalaan River is in good quality and classified as A level, except for the value of BOD 19,065 mg/l at the point A and 28,095 mg/l at the point B that are higher than that of the tolerable maximum value (BOD) 3 mg/l. The appeal of natural attractions that draw on the Pulau Pinus area is the scenery, tourists who claimed it by 50%, while 45% said river. Travelers who visit by 55 % strongly agreed that if the Pulau Pinus region as one of tourism attractive power in South Kalimantan.Keywords : Water Quality, Nature tourism area, Tourist Perception